Osteocalcin and Matrix Gla Protein in developing teleost teeth. Identification of sites of mRNA and protein accumulation at single cell resolution - Ortiz-Delgado, J. B. (2014)
In this study, the tissue distribution and accumulation of osteocalcin or bone Gla protein (BGP) and matrix Gla protein (MGP) were determined during tooth development in a teleost fish, Argyrosomus regius. In this species, the presence ofBGP andMGPmRNAin teethwas revealed by in situ hybridization. mRNA for BGP was detected in the odontoblasts as well as in its cytoplasmic processes emerging through dentinal tubules,whilemRNA for MGP was expressed in the enamel portion within the apical portion of the elongated cell bodies of enameloblasts, adjacent to the root of the teeth as well as in cells within the pulpal space. Immunolocalization of BGP and MGP demonstrated that these proteins accumulate mainly in the mineralized dentin or in enameloblastic processes, confirming in situ hybridization results. In this study, we examined for the first time the localization of both BGP and MGP gene expression and protein accumulation within the different regions of the vertebrate tooth. We clearly demonstrated that although the overall pattern of BGP andMGPgene expression and protein accumulation in A. regius teeth was in general agreement to what is known for other vertebrates such as rats or rodents, our study provided novel information and highlighted some species-differences between fish and higher vertebrates.